Responsive Evaluation Of The Microleading Program In Strengthening Leadership Competence Of Islamic Education Management Students - Faidhur Rohim; Achmad Hanuji Akbar; Suwadi (JIEMAN: Journal of Islamic Educational Management, 2025)
This study aims to evaluate the Microleading Program as a form of practice-based learning in the Islamic Education Management Study Program, Faculty of Tarbiyah and Teacher Training, UIN Kiai Haji Achmad Siddiq Jember. This program is designed to equip students with administrative skills through work simulations in an educational laboratory environment. The evaluation model used is Responsive Evaluation from Robert Stake, which emphasizes understanding stakeholder experiences and perceptions as the basis for assessing the success of the program. This study uses a qualitative approach with an evaluative case study type. Data was collected through interviews, observations, and documentation, with the main informants consisting of participating students, teaching lecturers, and choirs. Study Program. The results of the study show that the program runs according to the guidelines and has succeeded in forming students' basic competencies in the field of educational administration. In addition to technical impacts, affective impacts were also found such as increased confidence, ability to work together, and maturity of professional attitudes. However, the implementation of the program also faces obstacles in the form of limited facilities, lack of student involvement in planning, and variations in the quality of mentoring between classes. This research makes a theoretical contribution to the development of a more participatory and contextual educational evaluation model, and confirms that micro-work simulation programs can be a strategic means in the formation of student professional leadership. These findings provide a new direction for the evaluation of practice-based programs in Islamic higher education that are more responsive to the needs of participants and changing times.